Start by integrating y'' twice to get function y(x).
[tex]y' = \int (12x - 2) dx = 6x^2 -2x + c \\ \\ y = \int (6x^2 -2x+c )dx= 2x^3-x^2 +cx+d[/tex]
Next find value of coefficients 'c' and 'd' using the given tangent line
The slope of tangent line is equal to y' when x=1.
[tex]6x^2 -2x+c = -1, x = 1 \\ \\ 6-2+c = -1 \\ \\ c = -5[/tex]
The tangent line intersects the curve y(x) when x = 1.
If x = 1, then y = 4 (From y =-x+5)
[tex]y = 2x^3 -x^2-5x +d , x = 1, y = 4 \\ \\ 2-1-5+d = 4 \\ \\ d = 8[/tex]
Final Answer:
[tex]y = 2x^3 -x^2 -5x+8[/tex]